2019
DOI: 10.1108/ijppm-03-2018-0124
|View full text |Cite
|
Sign up to set email alerts
|

The employee engagement and OCB as mediating on employee performance

Abstract: Purpose The purpose of this paper is to examine the effect of ethical leadership on employee performance, with the employee engagement and organizational citizenship behavior (OCB) as mediating variables. Design/methodology/approach The design of this study was to ascertain the predictive generalizations truth of the theory. The population in this study was all employees of non-star hotels in Sarbagita area of Bali. Findings First, ethical leadership does not have a significant effect on employee performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 57 publications
2
11
0
3
Order By: Relevance
“…The findings also indicated that employee engagement could affect OCB positively in the time of COVID-19. This result agrees with previous studies which indicated the role of employee engagement at work in predicting OCB during the pandemic [97,131,132]. Furthermore, the findings of this study related to the impact of affective commitment on OCB agrees with the result of previous studies [60,[70][71][72].…”
Section: Discussionsupporting
confidence: 93%
“…The findings also indicated that employee engagement could affect OCB positively in the time of COVID-19. This result agrees with previous studies which indicated the role of employee engagement at work in predicting OCB during the pandemic [97,131,132]. Furthermore, the findings of this study related to the impact of affective commitment on OCB agrees with the result of previous studies [60,[70][71][72].…”
Section: Discussionsupporting
confidence: 93%
“…The level of success that can be achieved by an institution with regards to its strategic objectives is entirely dependent on the way those who work for it perform (Sugianingrat et al, 2019). Empirical proof with regards to the tri-lateral link between Human Resources Management, the well-being of employees, and their performance reflects the fact that HRM plays a positive role on the various dimensions of employee performance.…”
Section: Employee Performancementioning
confidence: 99%
“…In their investigation of IT organizations in India, the authors explain that when employees feel their supervisor support, equity and care, they reciprocate by becoming more engaged to their work and subsequently their OCB increases as they are more willing to do extra effort beyond their job description. Furthermore, in the field of hospitality management, Sugianingrat et al (2019) confirmed that ethical leadership increases employee engagement which consequently enhances employee OCB. Authors explicate that when employees perceive the ethical behavior of their manager, they show more respect toward him; their sense of attachment and engagement to their organization is enhanced.…”
Section: P8 Increase In Frontline Engagement Reduces Employees' Intention To Quitmentioning
confidence: 85%
“…Managers should enhance employees' self-efficacy by encouraging them and providing them with positive feedback. The aforementioned have been recently emphasized (Kapil & Rastogi, 2019;Sugianingrat et al, 2019).…”
Section: Practical/managerial Implicationsmentioning
confidence: 99%